2004
DOI: 10.1051/animres:2003044
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements of whole linseed and vitamin E to increase levels of -linolenic acid and vitamin E in bovine milk

Abstract: -The potential to increase the concentrations of n-3 polyunsaturated fatty acids (PUFAs) in milk fat was investigated by studying the effects of feeding a xylose-treated, whole cracked linseed supplement (rich in α-linolenic acid) to dairy cows. Also the effect of increasing the dietary intake of vitamin E on the vitamin E status of milk was investigated. The effect of pasteurisation on milk fatty acid composition was also examined. Using a 3 × 2 factorial design, a total of 60 Holstein dairy cows were fed a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…Thus, when the linseed oil amount was increased from zero to 1.5 and 3.0% of diet DM, the 18:3n-3 response in milk was not increased proportionally to the oil intake (Tab. 3), and increasing xylose-treated, whole cracked linseeds from 8 to 21% of the diet only slightly increased milk 18:3n-3 (10.5 g/100 g FA) [150].…”
Section: Linolenic Acid and Long-chain N-3 Famentioning
confidence: 86%
“…Thus, when the linseed oil amount was increased from zero to 1.5 and 3.0% of diet DM, the 18:3n-3 response in milk was not increased proportionally to the oil intake (Tab. 3), and increasing xylose-treated, whole cracked linseeds from 8 to 21% of the diet only slightly increased milk 18:3n-3 (10.5 g/100 g FA) [150].…”
Section: Linolenic Acid and Long-chain N-3 Famentioning
confidence: 86%
“…Earlier studies have demonstrated that whole or processed linseeds in the diet reduce milk protein output (Deaville et al, 2004;Akraim et al, 2007) because of reductions in both milk yield and milk protein content. In the present study, there was no change in milk protein concentration possibly owing to the relatively low linseed oil intake as compared with the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, increases of milk α-linolenic acid have been modest except for in one study (Mele et al, 2007). Increasing the level of α-linolenic acid in milk from ruminants seems difficult because of the relatively low transfer rate of this FA from the diet into milk (Palmquist, 2006;Sanz-Sampelayo et al, 2007) and the dietary inclusion constraints necessary to avoid negative effects on rumen fermentation and milk yield (Deaville et al, 2004;Gonthier et al, 2005).…”
Section: Introductionmentioning
confidence: 95%